Thermal comfort index in lactating cows in an adapted free-stall facility - Carvalho Vasconcelos, João Marcos de; Ferreira, Sindynara; Rezende, Elisa de Souza Junqueira; Pereira, José Luiz de Andrade Rezende (Revista Agrogeoambiental, 2020)
This study was conducted to investigate the thermoregulation of Holstein cattle in an adapted free-stall facility at IFSULDEMINAS, Campus Inconfidentes, by measuring thermal comfort indices. The experimental period was from the end of December 2012 to the start of January 2013, in a total of 16 days. 12 multiparous, lactating, black-and-white Holstein cows were used in a free-stall system. Rectal temperature, respiratory frequency, ambient temperature and relative humidity were recorded at 3:00 a.m., 7:00 a.m., 11:00 a.m., 3:00 p.m., 7:00 p.m. and 11:00 p.m. The results demonstrate that despite the temporal variations that occurred throughout the evaluation days, the confined animals maintained their body temperature in balance.